Evaluating the quality of conduct of systematic reviews on the application of transcranial magnetic stimulation (TMS) for aphasia rehabilitation post-stroke - Georgiou, Anastasios M.; Lada, Eleni; Kambanaros, Maria (My University, 2019)
Background: Noninvasive brain stimulation techniques such as repetitive transcranial magnetic stimulation (rTMS) are used to facilitate the recovery of language in stroke patients with aphasia. Although rTMS is a promising therapeutic method, further investigations are needed to expand the knowledge base about the use of the technique in stroke-induced aphasia. Aims: To evaluate the quality of conduct of systematic reviews of randomized controlled trials (RCTs) of interventions on the application of rTMS for aphasia rehabilitation post-stroke using the AMSTAR 2 (A Measurement Tool to Assess Systematic Reviews) instrument. Methods & Procedures: A search was performed of databases specific to systematic reviews. Four systematic reviews met the inclusion criteria. All aspects regarding the conduct of each individual systematic review was critically appraised using the AMSTAR 2 instrument. Outcomes & Results: The overall confidence ratings based on weaknesses in critical domains identified by the AMSTAR 2 was low for one systematic review and critically low for the remaining three. Conclusions: The quality of conduct of published systematic reviews of RCTs on the application of rTMS for aphasia rehabilitation post-stroke is low. The evidence for the effectiveness of rTMS on language recovery post-stroke remains inconclusive. The findings underscore the need for methodologically rigor trials on the applicability of TMS as an intervention approach for aphasia. Published guidelines to provide reliable and replicable results are urgently needed.
Keywords: Non-invasive brain stimulation (NIBS); RCTs; scientific rigour